Sequential dual-locking strategy using photoactivated Pt(IV)-based metallo-nano prodrug for enhanced chemotherapy and photodynamic efficacy by triggering ferroptosis and macrophage polarization - Jun Li; Qiang Zhang; Hao Yang; Wenli Lu; Yulong Fu; Yingcai Xiong; Xuan Wang; Tianming Lu; Yanlin Xin; Zejuan Xie; Weichao Chen; Guoqiang Wang; et al. (Elsevier, 2024)
Selective activation of Pt(IV) prodrugs within tumors has emerged as a promising strategy in tumor treatment. Although progress has been made with photo- and ultrasound-activated Pt(IV) prodrugs, concerns remain over the non-specific activation of photosensitizers (PS) and the potential for phototoxicity and chemical toxicity. In this study, a sequential dual-locked Pt(IV) nano-prodrug that can be activated by both the acidic tumor microenvironment and light was developed. The Pt(IV) prodrug was prepared by conjugating PS-locked Pt(IV) to a polymeric core, which was then chelated with metallo iron to lock its photoactivity and form a metallo-nano prodrug. Under acidic tumor microenvironment conditions, the metallo-nano prodrug undergoes dissociation of iron, triggering a reduction process in oxaliplatin under light irradiation, resulting in the activation of both chemotherapy and photodynamic therapy (PDT). Additionally, the prodrug could induce metallo-triggered ferroptosis and polarization of tumor-associated macrophages (TAM), thereby enhancing tumor inhibition. The dual-lock strategy employed in a nanoparticle delivery system represents an expansion in the application of platinum-based anticancer drugs, making it a promising new direction in cancer treatment.